1013 Occupational tuberculosis in south africa: are healthcare workers adequately protected?. (24th April 2018) - Malotle, MM; Spiegel, J; O'Hara, L; Adu, P; Yassi, A; Zungu, M; Bryce, E
Abstract : Introduction: Effective tuberculosis (TB) infection prevention and control (IPC) measures including education and training are crucial in limiting the spread of TB in healthcare settings. We aimed to explore how well HCWs adhere to TB IPC practices, the nature and extent of training related to TB IPC across demographic and occupational factors. Method: An interviewer-driven structured survey was conducted among HCWs in a provincial tertiary hospital in Gauteng Province, South Africa. Data were analysed using SPSS version 24. Pearson's Chi Square test or Fisher's exact tests checked differences between categorical variables; logistic regression assessed associations between covariates. Results: Of the 285 HCWs surveyed, only 43% reported having received training on TB transmission, signs and symptoms; 29.8% of nurses had been trained on the proper use of N95 respirators; only 5% of support workers were trained on mode of transmission; and only 37.2% of all HCWs were aware of a protocol for managing TB patients. Only 56.3% of nurses and 66.7% of doctors reported they always or sometimes wore respirators when managing suspected or confirmed TB cases, although 70.5% of the nurses and 86.7% of the doctors reported that these personal protective equipments were not readily available. Importantly, non-clinical (support) HCWs were more than 7 times more likely to use respirators if trained on their proper use. Discussion: Major gaps persist in both availability of respirators and training of HCWs on TB transmission, both factors highly associated with lack of adherence to TB IPC. To protect HCWs, hospital management should ensure availability of respirators as well as effective trainings for all job categories, with particular attention to support staff, who seem to be particularly poorly trained and at high risk of TB.